A 7th Century BCE Bulla Fragment From Area D3 in The ‘City Of David’/Silwan - Yuval Gadot; Yuval Goren; Oded Lipschits (Journal of Hebrew Scriptures, 2013)
A bulla fragment was found in the excavations of Tel Aviv University at the City of David/Silwan. It is made out of local terra rossa soil, and the reading is: קם // ---לך --- The names אחיקם and אליקם are the best candidates for the name in the upper register. The title “עבד המלך” is the best candidate for the title in the lower register. The seal's quality and the reconstructed title of its bearer indicate that it was used by a high official in the royal Judahite administration.